Poisson random sums in modelling operations for the treatment of ongoing risk occurrences - Αρτίκης Κωνσταντίνος Τ.; Αρτίκης Παναγιώτης Τ. (SPOUDAI Journal of Economics and Business, 2005)
The paper makes use of a very important result from stochastic theory of service systems in order to formulate a Poisson random sum of nonnegative random variables. Applications of the proposed Poisson random sum in stochastic modelling of risk financing operations for ongoing risk occurrences at given time point are provided. JEL Classification: C51